21st Century Environmental Education: A Strategy for Transforming Community Behavior in Facing the Environmental Crisis - Eka Apriyanti; Erian Fatria; Agus Priadi; Ikhwan Ridha Wilti (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The background of this investigation refers to the unwise human behavior towards the environment that has a significant impact on environmental crises and disasters. This behavior has made the condition of the ecosystem order worse and no longer able to meet the needs of all its components. Therefore, a strategy is needed in transforming human knowledge, attitudes and behavior so that the environment remains sustainable and sustainable. 21st century environmental education comes as a resolution in solving environmental problems. The purpose of this investigation is to provide information to the public about the urgency of 21st century environmental education in achieving SDGs. The method of investigation is Literature Review (LR). Articles used in the review of this paper were obtained from online databases. The results of the investigation obtained are that the implementation of 21st century environmental education responds to challenges and adapts to the needs of society, especially in dealing with environmental crises that occur due to anthropogenic activities. Strategies, approaches, and models of 21st century environmental education are adapted to the needs of society and the development of technology and information. The movement of the environmental education paradigm towards ESD is expected to transform the way of thinking and working towards a green future. The resulting conclusion is that empowering people's knowledge, attitudes and behaviors through 21st century environmental education must be done immediately in order to achieve a balance of environmental quality and the quality of human life.